2022
DOI: 10.3390/ijms23168954
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Activation in Vascular Insulin Resistance and Dysfunction

Abstract: Systemic insulin resistance is characterized by reduced insulin metabolic signaling and glucose intolerance. Mineralocorticoid receptors (MRs), the principal receptors for the hormone aldosterone, play an important role in regulating renal sodium handling and blood pressure. Recent studies suggest that MRs also exist in tissues outside the kidney, including vascular endothelial cells, smooth muscle cells, fibroblasts, perivascular adipose tissue, and immune cells. Risk factors, including excessive salt intake/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 72 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…Experiments on isolated pancreatic islets revealed that aldosterone acting on mineralocorticoid receptors (MR) enhances glucose-induced insulin secretion and ROS production. The activation of MR also decreased the sensitivity to insulin in adipocytes and in skeletal muscles [116], and promoted the development of inflammation, oxidative stress, lipid disorders, and insulin resistance, thereby impairing vascular insulin metabolic signaling [15,117,118].…”
Section: The Role Of Ang II In Experimental Obesity Diabetes Mellitus...mentioning
confidence: 99%
“…Experiments on isolated pancreatic islets revealed that aldosterone acting on mineralocorticoid receptors (MR) enhances glucose-induced insulin secretion and ROS production. The activation of MR also decreased the sensitivity to insulin in adipocytes and in skeletal muscles [116], and promoted the development of inflammation, oxidative stress, lipid disorders, and insulin resistance, thereby impairing vascular insulin metabolic signaling [15,117,118].…”
Section: The Role Of Ang II In Experimental Obesity Diabetes Mellitus...mentioning
confidence: 99%
“…Action of aldosterone on T channels is presumably indirect, because the gene CACNA1h, which is coding for the CaV3.2 T type channel does not possess mineralocorticoid response element (MRE). Increased formation of reactive oxygen species (ROS) and their involvement in the regulation of affinity of steroid hormones to MR receptors should be also taken into consideration [63][64][65][66]. In the cardiovascular system the genomic and nongenomic effects of aldosterone are also modified by angiotensin II (Ang II) [35].…”
Section: Genomic and Nongenomic Actions Of Steroid Hormonesmentioning
confidence: 99%
“…Studies indicate that aldosterone excess can lead to insulin resistance. [32][33][34] Although metformin is clinically employed to address insulin resistance, given the patient's concurrent diabetic nephropathy and elevated lactate levels (2 mmol/L), Considering the potential risk of lactic acidosis, [35] the inclusion of metformin in this treatment has been withheld. SGLT-2 inhibitors lower blood glucose by inhibiting renal proximal tubular reabsorption of glucose and sodium, potentially exacerbating the patient's hypotensive symptoms (101/65 mm Hg).…”
Section: Gs Combined With Diabetesmentioning
confidence: 99%